The criterion of pedagogical calling for the selection of future teachers - Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 1998)
The idea of the article is to show that pedagogical calling is a relevant criterion for selection of future teachers. This notion is developed from a theoretical analysis and the results of the research dealing with pedagogical calling. Revealing the essence of pedagogical callings as well as its structure (a combination of personality’s features; namely, motivation, potentiality and character) and the peculiarities of its manifestation in pedagogical work and activity are supposed to strengthen the central idea of the article.